Tuna (Mo Luna) dan Relevansinya Terhadap Pembelajaran IPS - Olfin Anuke; Ismaul Fitroh (Departement of Mathematics Education, 2023)
Tuna (Mo luna) is one of the traditions of Gorontalo People. Tuna (Mo luna) in Indonesian which means circumcision is an activity of removing some of the skin at the end that covers the head of the male genitals. This research uses literature study and interview methods. The results of the study show that the purpose of the circumcision tradition is not only to obey with religious orders, but also to prevent dirt from accumulating in the male genitals. Related to religious orders, the majority of Gorontalo People embrace Islam so that this tradition continues to be sustainable today. In carrying out the Tuna tradition (Mo luna) there are character values such as mutual cooperation and social interaction in it. This is in line with the material in social studies learning. In the matter of national cultural diversity in Elementary School Social Studies can be instilled Tuna (Mo Luna) values in students.